Do you watch or play? Towards a new model of university (Journal of Parents and Teachers, 2013)
Ibai Martinez, a 22 years old entrepreneur and studentof a new university degree called LEINN, writes about the key pointsto evolute the university model of nowadays
Keywords: education; team work; innovation; teachers; technology